Aprendo a sumar, restar, multiplicar y dividir - Lofret, Esteban H. (Buenos Aires : Imaginador, 2007)
Learning about numbers, adding, substracting, multiplication and division. For primary (K-3) school children.
Keywords: Mathematics -- Juvenile literature; Arithmetic -- Juvenile literature; Mathematics; Arithmetic; Matematicas -- Literatura juvenil; Aritmetica -- Literatura juvenil